The Emerging Roles of Rad51 in Cancer and Its Potential as a Therapeutic Target - Wang, Ziyi; Jia, Renxiang; Wang, Linlin; Yang, Qiwei; Hu, Xiaohai; Fu, Qiang; Zhang, Xinyu; Li, Wenya; Ren, Yi (Frontiers in Oncology, 2022)
Defects in DNA repair pathways are emerging hallmarks of cancer. Accurate DNA repairs and replications are essential for genomic stability. Cancer cells require residual DNA repair capabilities to repair the damage from replication stress and genotoxic anti-tumor agents. Defective DNA repair also promotes the accumulation of genomic changes that eventually lead to tumorigenesis, tumor progression, and therapeutic resistance to DNA-damaging anti-tumor agents. Rad51 recombinase is a critical effector of homologous recombination, which is an essential DNA repair mechanism for double-strand breaks. Rad51 has been found to be upregulated in many malignant solid tumors, and is correlated with poor prognosis. In multiple tumor types, Rad51 is critical for tumor metabolism, metastasis and drug resistance. Herein, we initially introduced the structure, expression pattern of Rad51 and key Rad51 mediators involved in homologous recombination. Additionally, we primarily discussed the role of Rad51 in tumor metabolism, metastasis, resistance to chemotherapeutic agents and poly-ADP ribose polymerase inhibitors.